Laguna : Kingpin sa loob ng mga pahina a case study on former Laguna governor ER Ejercito and content analysis on his governorship as reported by Laguna Courier, Los Baños Times and Makiling Journal - Parico, Jenicca Rose Cabiling; Parico, Jenica Rose Cabiling; Rola, Alyssa Marie Casiple (2015)
"This study focuses on former Laguna governor emilio Ramon 'ER' Ejercito as a case for celebrity and patronage or dynasty politics in Laguna. The research aims to explain how three local newspapers, Laguna Courier, Los Banos Times and Makiling Journal framed the news over his governorship from February 2013 to June 2014. News articles regarding Ejercito written in the three publications from the initial campaign period of February 2013 until a month after his vacation of office last June 2014 were analyzed through content analysis. Interviews with the editors of Laguna Courier, LB Times and Makiling Journal were also included to provide context on how news framing methods were done in reporting. This study explores the connection between local politics and local media as analyzed using the common themes in the published articles of the community press. The research takes a look at how Laguna community journalists try to uphold journalistic values such as truth-telling and media independence without being influences by famous icons. Moreover, it also aims to present ER Ejercito as an epitome of the current situation of celebrity and patronage politics in Laguna."